I pledge allegiance - Lynch, Chris, 1962- (New York, NY : Scholastic Inc., 2012)
Best friends Morris, Rudi, Ivan, and Beck, having been either drafted or enlisted in the military during the Vietnam War, pledge they will come home together, and Morris, a sailor on the USS "Boston," relies on that promise to stay strong while his courage and resolve are tested under attack.
Wilson's Junior High School, October 2012
School Library Journal, January 2012
Booklist, October 2011
Bulletin (Center for Children's books), December 2011
Teacher Librarian, December 2011
Kirkus Review, October 2011
Keywords: Vietnam War, 1961-1975 -- Juvenile fiction; Friendship -- Juvenile fiction; Vietnam War, 1961-1975 -- Fiction; Friendship -- Fiction; War -- Fiction; Vietnam War, 1961-1975 -- Fiction; Friendship -- Fiction; War stories; War stories